Efeito local e sistêmico do laser de baixa potência (830nm) no limiar de dor por pressão em indivíduos saudáveis: estudo prospectivo, controlado, randomizado - Pelegrini, Stella (2012)
Introduction: The low-power laser (LBP) is used as a therapeutic treatment for pain control. However, it is still questioned about the real effect and also the dosimetry more effective for this analgesic effect. Objective: To evaluate the local effect and systemic of LBP in pressure pain threshold in healthy subjects. Methods: 150 subjects randomized in 5 groups (n=30 per group): control, placebo laser, 3J, 6J, 12J. As an instrument for evaluate the pain was used a pressure algometer in five different times. In the region of the dominant hand of the individual and the laser was held algometry to determine the effect local and region of the dominant leg was held algometry to check only the systemic effect of LBP. Results: There was a reduction in local pressure pain threshold in the group 3J compared with control groups (p=0.0016) and placebo (p=0.004) and no systemic change on pressure pain threshold. Conclusion: LBP when used with energy 3J reduced the pain threshold by local pressure in healthy subjects, but there was no systemic illness. Keywords: laser therapy, pain measurement, pain threshold, analgesia